Biology and Management of Creeping Beggarweed (Desmodium incanum) in Warm-Season Turf - Grantly Ricketts; Chris Marble (EDIS)
Creeping beggarweed is a common perennial broadleaf weed in Florida landscapes, home gardens, pastures, and other agricultural production systems. This new 6-page article is written for green industry professionals and others to help aid in the identification and management of creeping beggarweed in landscape turf and planting beds. Written by Grantly Ricketts and Chris Marble, and published by the UF/IFAS Environmental Horticulture Department. https://edis.ifas.ufl.edu/ep591